2019
DOI: 10.1186/s40643-019-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage protection: an excellent application of bioactive compounds

Abstract: Discovery of deoxyribonucleic acid (DNA) solved out the mystery of cellular functioning and abnormality in cellular metabolism. Understanding the coding of DNA resulted in enormous medical growth and helps the researchers in finding the genes which trigger major chronic diseases in humans. Further, the structural and sequential analysis brought humans into a new era of medical industry. The advancement in understanding of DNA could be a boon for agricultural sector as it allowed the farmers/breeders to choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 144 publications
(124 reference statements)
0
18
0
Order By: Relevance
“…The protection of DNA indicated the presence of flavonoids and phenolic compounds like trycin and quercetin in H. shulli seeds which can prevent the production of ROS by complexing cations [ 44 ]. Extracts prepared from black raspberry [ 45 ] seed and various natural resources [ 46 ] could either stop or slow down the process of DNA damage. So these results indicate that H. schulli seeds is a potential source of antioxidants that prevent DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The protection of DNA indicated the presence of flavonoids and phenolic compounds like trycin and quercetin in H. shulli seeds which can prevent the production of ROS by complexing cations [ 44 ]. Extracts prepared from black raspberry [ 45 ] seed and various natural resources [ 46 ] could either stop or slow down the process of DNA damage. So these results indicate that H. schulli seeds is a potential source of antioxidants that prevent DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Breakage in plasmid DNA is also one of the critical parameter in determining the genotoxicity of wide range of chemicals and this test is very commonly used in environmental monitoring [89][90][91][92] . Incidence of DNA damage is profound indicator of potential risk of malignancy in human being 93 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, pigmented rice has become more popular than non-pigmented rice due to its potential for healthy foods. Previous studies reported that pigmented rice has higher protein content than non-pigmented rice [3] . Moreover, its antioxidant activities and phytochemical contents are higher than nonpigmented rice [1] .…”
Section: Introductionmentioning
confidence: 88%